The Constructive Destruction of a Sold Usurped Property to a Bona Fide Purchaser in the Balance of Jurisprudential Critique (The Criticism of the Proposed Bill of the Amendment of Article 323 of Civil Code) - Atefeh Ajori Ayask; sedighe mohamadhasani (آموزه‌‌های فقه مدني)
The usurper in Shīʿite jurisprudence is obliged to return the specified usurped property, except in the case of destruction (both factual and constructive) of the usurped object. Article 323 of Civil Code based on this, considers purchaser of the usurped property as a usurper which the owner can refer to him for the return of the specified object. A proposed bill, however, based on the amendment of the above article has been submitted to the parliament in order to protect the validity of the official document and protect the rights of a bona fide purchaser, according to which the usurped property that has been transferred through drawing up and making an official document and the customer is ignorant of its usurpation is considered as a destructed object and the owner is only entitled to its price, which can only refer to the “usurper purchaser” to receive it. The aforementioned proposed bill is controversial in terms of jurisprudential foundations, which is examined in the present article by a descriptive-analytical method and using original jurisprudential sources, because the criterion for the realization of constructive destruction is the occurrence of an intellectual or religious impediments in the return of the existing object. “Capable of being owned exceeding,” “impossibility,” “bodily injury,” “Destruction of a property with a known owner,” and “Destruction of a usurper’s property especially in the assumption of destruction and demolition of his/her considerable property” are among intellectual or religious impediments to the restitution of a specified object and cause the realization of the title of constructive destruction, but the mere “transferring acts” due to the forcible illegitimate possession of the usurper does not lead to the realization of the religious impediment and consequently, the title of a constructive destruction about a usurped specified object. In addition, in the case of the constructive destruction of a usurped specified object, the customer, whether ignorant or knowledgeable along with the usurper purchaser is the liable and responsible for something identical (fungible) or the price of the usurped property and merely ignorance will not be removed his/her liability.